Malaysian guidelines on the use of human biological samples for research - Muhammad Amjad, Nasser; Abdul Rahman, Suzanah (National Institutes of Health, Ministry of Health Malaysia, 2025)
The Malaysian Guidelines on the Use of Human Biological Samples for Research have played a pivotal role in ensuring the ethical, safe, and responsible use of human biological materials in scientific research. As the landscape of biomedical research evolves rapidly, the need to adapt to new technologies, methodologies, and regulatory standards has become paramount. The new edition of these guidelines represents a critical step forward in addressing these changes while upholding the fundamental principles of respect, dignity, and rights for individuals contributing to scientific progress. The world of medical and scientific research continues to transform, with advancements in genomics, biotechnology, and personalized medicine paving the way for innovative treatments and health solutions. However, with these advancements come new ethical challenges, particularly in relation to consent, privacy, and the potential for misuse of biological samples and data. As such, the guidelines remain an essential framework for ensuring that research using human biological samples is conducted with the highest standards of integrity, transparency, and respect for humanity. This revised edition reflects extensive consultations with experts from diverse fields, including bioethics, law, and medicine, and incorporates the latest best practices and international standards. It offers clear, comprehensive, and practical guidance for researchers, institutional review boards, and policymakers, empowering them to navigate the complexities of modern research environments while safeguarding the welfare of individuals who voluntarily contribute to the advancement of knowledge. As we look to the future of biomedical research in Malaysia and globally, the importance of maintaining a delicate balance between scientific progress and ethical responsibility cannot be overstated. These guidelines are a vital resource in achieving that balance. By following these principles, we ensure that the pursuit of knowledge remains aligned with the values of justice, respect, and care for humanity.